Current options concerning the endodontically-treated teeth restoration with the adhesive approach - Marco Aurélio de Carvalho; Priscilla Cardoso Lazari; Marco Gresnigt; Altair Antoninha Del Bel Cury; Pascal Magne (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract: Adhesive procedures have changed the way to restore endodontically treated teeth (ETT). It started with the shift from cast post-and-core to fiber post. The original focus on strength also shifted towards failure modes, revealing that catastrophic failures are still a concern when restoring endodontically-treated teeth even with fiber posts. As an alternative, postless approaches have been proposed in order to improve the chances of repair. The goal of this critical review is to present a survey of the current knowledge on adhesive approaches to restore endodontically treated teeth with and without extensive coronal tissue loss. The preservation of tooth structure of endodontically treated teeth is paramount. Partial versus full coverage of ETT, the role of the ferrule, the post type effect on catastrophic failures and postless alternatives as endocrowns and postless build-ups are reviewed. There is a consensus that the remaining tooth structure plays an important role in ETT survival, although the current literature still is contradictory on the influence of post type on root fractures as well as the benefits of avoiding a post or partially restoring a tooth. More clinical studies should be carried out with the modern postless adhesive alternatives to conventional approaches.